Roles of novel biomarkers in progression of cutaneous squamous cell carcinoma - Farshchian, Mehdi (Annales Universitatis Turkuensis D 1179, 2015)
Roles of novel biomarkers was studied in progression of cutaneous squamous cell carcinoma (cSCC) as the most common metastatic skin cancer. The incidence of cSCC is increasing worldwide due to lifestyle changes such as recreational exposure to sunlight and the aging of the population. Because of an emerging need for molecular markers for the progression of cSCC, we set our goal to characterize three distinct novel markers overexpressed in cSCC cells. Our results identified overexpression of serpin peptidase inhibitor clade A member 1 (SerpinA1), EphB2 and absent in melanoma 2 (AIM2) in cSCC cell lines compared with normal human epidermal keratinocytes (NHEKs). Immunohistochemical analysis of SerpinA1, EphB2 and AIM2 revealed abundant tumor cell-specific expression of cytoplasmic SerpinA1 and AIM2 and cytoplasmic and membranous EphB2 in cSCC tumors in vivo. The staining intensity of SerpinA1, EphB2 and AIM2 was significantly stronger in cSCC as compared with carcinoma in situ (cSCCIS) and actinic keratosis (AK). Tumor cell-associated SerpinA1 and EphB2 was noted in chemically induced mouse skin SCC, and the staining intensity was stronger in mouse cSCCs than in untreated skin. AIM2 staining intensity was significantly more abundant in cSCC of organ transplant recipients (OTR) than in sporadic cSCC in vivo. EphB2 knockdown resulted in inhibition of migration in cSCC cells. In addition, knockdown of EphB2 and AIM2 was found to inhibit the proliferation and invasion of cSCC cells and to delay the growth and vascularization of cSCC xenografts in vivo. Altogether, these findings identify SerpinA1 as a novel biomarker for cSCC. In addition, characterization of the roles of EphB2 and AIM2 in the progression of cSCC was implicated them as possible therapeutic targets for the treatment of cSCC particularly in unresectable and metastatic tumors.

Ihon levyepiteelisyövän kehittymiseen liittyvät uudet merkkitekijät Keratinosyyttiperäinen ihon okasolusyöpä on yleisin metastasoituva ihosyöpä. Sen ilmaantuvuus kasvaa maailmanlaajuisesti elintapojen muutoksen kuten auringonvalolle altistumisen sekä väestön ikääntymisen takia. Tarvitaankin uusia merkkitekijöitä tämän syövän etenemisen ennustamiseksi. Työssämme löysimme kolme uutta merkkitekijää ja selvitimme niiden roolia ihon okasolusyövässä. Havaitsimme, että seriiniproteaasin estäjä A1 (SerpinA1), EphB2 ja absent in melanoma 2 (AIM2) ovat voimakkaasti koholla ihon okasolusyövästä eristetyissä solulinjoissa verrattuna ihmisen normaaleihin epidermaalisiin keratinosyytteihin. Tämän ohella havaitsimme immunohistokemiallisessa analyysissä SerpinA1:n, EphB2:n ja AIM2:n ilmentyvän spesifisti kasvaimen soluissa sekä ilmentyvän merkitsevästi enemmän okasolusyövissä verrattuna in situ karsinoomaan ja aktiiniseen keratoosiin in vivo. Lisäksi SerpinA1:n ja EphB2:n havaittiin olevan yliekspressoituja hiiren ihoon kemiallisesti aiheutetussa okasolusyövässä. AIM2:n värjäytymisintensiteetti oli merkitsevästi voimakkaampi elinsiirtopotilaista peräisin olevissa ihon okasolusyövissä kuin sporadisissa okasolusyövissä. EphB2:n hiljentäminen esti merkitsevästi okasolusyövästä eristettyjen solujen migraatiota. Lisäksi EphB2:n ja AIM2:n hiljentäminen syöpäsoluissa vähensi merkitsevästi solujen jakaantumista ja invaasiota sekä tuumorien vaskularisaatiota ja kasvua xenograftimallissa in vivo. Yhdessä nämä havainnot antavat aiheen otaksua, että SerpinA1 voisi toimia merkkitekijänä ihon okasolusyövässä. Lisäksi havaitsimme, että EphB2:lla ja AIM2:lla on tärkeä rooli ihon okasolusyövän kehittymisessä, joten ne voisivat mahdollisesti toimia uusina hoidon kohteina erityisesti metastaattisten ja vaikeasti kirurgisesti poistettavien ihon okasolusyöpien hoidossa.